Influence of Internal Control Activities And Characteristics Of Audit Committee On The Quality Of Audit Implementation By A Public Accounting Firm - Poppy Sofia; Ilya Avianti (Jurnal Akuntansi, 2019)
The purpose of this study is to examine the Influence of Internal Control Activities and The Characteristics of The Audit Committee on The Quality of Audit Performed by aPublic Accountant Firm by conducting asurvey on General Insurance Companies in Indonesia. The method used is descriptive analysis. Ourpopulation is made of Internal Auditors and Audit Committee of General Insurance Companies in Indonesia registered onthe Financial Services Authority as of October 2017. We found out that The Characteristics of an Audit Committee had a positive and significant effect on The Quality of Audit Performed by aPublic Accountant Firm on General Insurance Companies in Indonesia. We fount also that Internal Control Activities and The Characteristics of the Audit Committee as a whole, have a positive and significant effect on The Quality of Audit Performed by aPublic Accountant Firm on General Insurance Companies in Indonesia.